If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying y = 8x + -4x Combine like terms: 8x + -4x = 4x y = 4x Solving y = 4x Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Simplifying y = 4x
| x^3+8x^2+22x+20=0 | | 4x-4x+3x-2x=11 | | 46=w-12 | | 2=5+3(7x-1) | | X^2=x^2+x-20 | | 1/2v-1/5=-2/3 | | Qxs=-340+10Px | | 52x-52x-6-6= | | (3/8)*45= | | 0.45/ln | | 14x+4x+2x-10x=20 | | 36=w-12 | | X-3y+2x+4= | | (5/8)*45= | | -y-6-3y-y= | | 14=5p+9p | | 19=5+3(7w+3) | | x^3+x^2-x-x-9=0 | | 2q+8q=90 | | 20=10(y-9) | | 18y-6+15y= | | 12=4z+2z | | 2sin(5x)cos(5x)=0 | | 54=8a+10a | | 48=4q+8q | | y=19x-16x | | 90=10w+8w | | 10=5(b-10) | | 10(x-2)-(x-4)= | | 3x^3+4x^2+6x=0 | | 5r+4r=90 | | 73=10r+3 |